First report of a Plasmodium malariae SSU rRNA gene variant in Africa associated with reduced amplification by nested PCR - Maki Goto; Kei Yamamoto; Kanako Komaki-Yasuda; Shigeyuki Kano; Norio Ohmagari (Tropical Medicine and Health)
Abstract Background Nested polymerase chain reaction (PCR) targeting the small subunit ribosomal ribonucleic acid (SSU rRNA, 18S rRNA) region is widely used to differentiate Plasmodium species. We identified a variant of the Plasmodium malariae SSU rRNA gene that suggests nested PCR may fail to detect P. malariae strains with unknown mutations. Case presentation A 56-year-old Japanese man developed a fever 2 months after returning from a 2-month stay in Sierra Leone. Quartan malaria was suspected based on blood smear findings, and nested PCR confirmed P. malariae infection. However, the secondary PCR band obtained using P. malariae-specific primers was fainter than the primary PCR band amplified with universal primers—a reversal of the typical pattern. Sequence analysis revealed a four-base deletion in the SSU rRNA gene within the primer-binding site of the species-specific reverse primer used in the secondary PCR, suggesting that mutations in this region may partially impair amplification and hinder species identification. Cytochrome b gene sequencing confirmed 100% identity with P. malariae. Conclusions These findings underscore the need for continued molecular surveillance and sequence-based validation to ensure accurate diagnosis of Plasmodium infections, particularly in regions where genetic variants and zoonotic strains are emerging.